NILAI-NILAI PLURALISME DALAM PENDIDIKAN ISLAM: BELAJAR DARI KEBERAGAMAN QIRA'AT 'ASYR - Dana Akhmad Dahlani; Abdul Muhid (Universitas Islam Lamongan, 2023)
The study of Qira'at 'Asyr is highly recommended for students who wish to comprehend the implicit diversity in the Qur'an. Using a comprehensive approach to this discipline, students must be active and proactive to serve as